Effects of detrital carbonate on stable oxygen and carbon isotope data from varved sediments of the interglacial Piànico palaeolake (Southern Alps, Italy) - Clara Mangili; Achim Brauer; Birgit Plessen; Peter Dulski; Andrea Moscariello; Rudolf Naumann (Journal of Quaternary Science, 2010)
Contamination with detrital matter is a well‐known bias in δ 18 O records from lake carbonates but quantitative information of this effect is yet lacking. Therefore, we developed a new methodological approach combining isotope analyses with microfacies, X‐ray diffraction and micro‐X‐ray fluorescence data and applied this in a case study for the Piànico interglacial lake record in order to provide a quantitative estimate of the effect of detrital carbonate on stable δ 18 O and δ 13 C data. The Piànico record contains a long series of distinct and well‐preserved calcite varves and is correlated to Marine Isotope Stage 11. Intercalated in the varve sequence are detrital layers triggered by surface erosion events. These detrital layers are mainly composed of dolomite, thus reflecting the mineralogical signature of the catchment. Microfacies analyses of a 9350 varve year interval allows the identification of detrital layers down to sub‐millimetre scale and a precise selection of three different types of samples for isotope analyses: (1) pure endogenic calcite varves (five varves per sample) without detrital contamination; (2) individual detrital layers; and (3) ‘mixed’ samples including five calcite varves and up to four thin detrital layers. Detrital samples show the isotopic signature of the catchment dolomite and are up to 5.7‰ enriched in δ 18 O values with respect to endogenic calcite samples. In mixed samples, the degree of isotopic enrichment is directly related to the amount of detrital contamination; δ 18 O of bulk carbonates is significantly biased when the detrital component amounts to more than 5% of the sample. It is also shown that samples containing detrital material have an influence on the calculation of the covariance between δ 13 C and δ 18 O. Covariance is high ( r = 0.76) when the correlation coefficient is calculated on the base of all samples, but absent ( r = −0.43) when samples containing detrital dolomite are excluded. It has been demonstrated that microfacies analysis is a quick tool to avoid or reduce detrital contamination in bulk carbonate samples during sample selection. Copyright © 2009 John Wiley & Sons, Ltd.